PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UKM INDUSTRI PENGOLAHAN KELAPA SAWIT DENGAN VARIABEL INTERVENING ORIENTASI PASAR - Desmita Desmita; Ria Nelly Sari; Rita Anugerah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this study is to prove the indirect effect of entrepreneurialorientation through SMEs performance. The population of this research is using industrypalm oil of Province Riau District. Method of sampling is using Cluster Sampling. Totalsampling 163 industry palm oil who have met the criteria as respondent to this research.This research uses the questionnaries to collect the data. Analysis of the data usedStructural Equation Modeling-Partial Least Square (SEM-PLS) with the software WarpPLS 5.0. to identify independent variables that influence the dependent variable andVariance Accounted For (VAF) analysis to detect whether an indirect relationshipthrough market orientation . The findings of the research showed that mediation wassignificant in market orientation in the correlation between entrepreneurial orientationon SMEs performance.Keywords : Entrepreneurial Orientation, Market Orientation, and SMEs Performance.